Improving Performance of the Braking Process, and Analysis Torque-Speed Characteristics of the Induction Motor - Al-Barbarawi, O. M. (Engineering, Technology & Applied Science Research, 2018)
This study aims to investigate, analyze, discuss and illustrate an effective and reliable fast braking system used in a three-phase induction motor by combining two or more different conventional braking methods such as dynamic-plugging and electromagnetic-plugging. The plugging process is implemented by disconnecting one of the stator phases and connecting it with an electromagnetic brake while interchanging the other two phases. The dynamic process is executed by inserting high resistance in the rotor circuit of the motor. The performance of the torque-speed characteristics of the induction motor will be studied and analyzed through the dynamic process. Mathematical models have been developed and simulated. Results show that the braking process time is greatly reduced.